2019
DOI: 10.1002/brb3.1312
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for chemotherapy‐induced peripheral neuropathy in patients receiving taxane‐ and platinum‐based chemotherapy

Abstract: Background Chemotherapy‐induced peripheral neuropathy (CIPN) is a significant and difficult to manage side effect of neurotoxic chemotherapies. Several risk factors for CIPN have been identified to date, but inconsistencies and methodological limitations exist in past research. Also, a limited number of potential risk factors has been investigated in the past. Aim The objective of this study was to assess the relative contribution of a wider range of risk factors in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
55
4
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 32 publications
(56 reference statements)
12
55
4
5
Order By: Relevance
“…This is in accordance with Mooney, Berry, Whisenant, and Sjoberg (2017) who demonstrated that using a questionnaire may contribute to intensifying symptom care and improve quality of life among the patients (Mooney et al, 2017). However, the outcome may rely on the ability to narrow or close the gap between the patients' and the professionals' estimation and grading of symptoms, a gap which in other studies is articulated as a crucial problem (Molassiotis et al, 2019;Mooney et al, 2017;Nyrop et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This is in accordance with Mooney, Berry, Whisenant, and Sjoberg (2017) who demonstrated that using a questionnaire may contribute to intensifying symptom care and improve quality of life among the patients (Mooney et al, 2017). However, the outcome may rely on the ability to narrow or close the gap between the patients' and the professionals' estimation and grading of symptoms, a gap which in other studies is articulated as a crucial problem (Molassiotis et al, 2019;Mooney et al, 2017;Nyrop et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…Multiple instruments have been developed to identify CIPN but no gold standard has been established, although it is common for physicians to use the scales of National Cancer Institute-Common Terminology Criteria Adverse Events (NCI-CTCAE) in their assessments of patients' adverse events. However, comparing a clinician-based grading system like the CTCAE scale with patient-reported outcome measures shows that professionals score patients' conditions lower than patient' themselves and thus identify fewer patients with CIPN (Molassiotis et al, 2019;Nyrop et al, 2019).…”
Section: Choice Of Instrumentmentioning
confidence: 99%
“…While there are established clinical risk factors for CIPN, none accurately predicts the severity of CIPN that an individual patient will have [4]. Cumulative dose is a strong risk factor for the development of CIPN with most neurotoxic antineoplastic drugs.…”
Section: Demographic and Clinical Predictors Of Cipnmentioning
confidence: 99%
“…Several demographic risk factors have been reported, including older age, obesity, and race. Older age was associated to longer paclitaxel‐induced peripheral neuropathy duration or increased severity in breast cancer, with the risk of severe neuropathy increasing by 5% per additional year in age in breast/ovarian cancer or by 13% per decade of life . A higher risk of TIPN has been identified in metastatic breast cancer patients aged >65 years .…”
Section: Introductionmentioning
confidence: 99%